DOI: 10.24124/2019/58995
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media engagement on university student recruitment

Abstract: Education marketing managers are increasingly becoming aware of the benefits of social media engagement in recruitment marketing for colleges and universities. Today's prospective student is tech-savvy and information driven. Despite a general emphasis on social media engagement in a university marketing strategy, there is minimal research on the influence it has on university student recruitment and the amount of effort that universities should dedicate to social media engagement. Therefore, this study focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the association between effective social media strategies and platforms and student enrollment decisions was not statistically significant. This implies that while effective social media strategies and platforms play a role in shaping student perceptions, they may not directly impact their enrollment decisions (Y Ahmadi, 2019). In addition, the study found a positive and significant association between university social media presence and effective social media strategies and platforms.…”
Section: Discussionmentioning
confidence: 75%
“…However, the association between effective social media strategies and platforms and student enrollment decisions was not statistically significant. This implies that while effective social media strategies and platforms play a role in shaping student perceptions, they may not directly impact their enrollment decisions (Y Ahmadi, 2019). In addition, the study found a positive and significant association between university social media presence and effective social media strategies and platforms.…”
Section: Discussionmentioning
confidence: 75%